Workplace health promotion - Talini, Donatella; Baldasseroni, Alberto (La Medicina del Lavoro, 2019)
Workplace Health Promotion (WHP-Workplace Health Promotion) is aimed at improving the  workers’ well-being and health, so as to guarantee conditions of greater psycho-physical well-being and work capacity for a future elderly population. Cost-benefit analysis studies indicate that the return of profits compared to the invested capital (Return of investment - ROI) can be very good. To conduct WHP’s activities successfully, the continuous and convinced commitment of all corporate subjects is required. WHP interventions must not represent alternative paths to those of Prevention and Safety, nor represent “discount” tools with respect to regulatory obligations. It is essential that there be clarity in the roles played by public institutions operators (USL / ASL / ATS) who, in various capacities and in various sectors, are involved. At the moment, in terms of WHP, the regions have responded differently and in any case the difficulties in applying the WHP to SMEs have become evident. Whatever the approach, WHP’s actions must take into account the end-point, ie the health gain of the workers involved due to the specific effect of the action promoted and for this reason the programs must provide an adequate follow-up, which becomes an element indispensable for any proposal. Health promotion in the “work” context has, with respect to more traditional contexts (such as school or community), undoubtedly peculiarities, which require a specific training of “health promoters” engaged in this field.